Chapter (De)globalizzazione e (dis)informazione. Le sfide all'analisi della politica estera nella politica contemporanea - Diodato, Emidio (Studi e saggi, 2022)
The chapter aims to provide an overview of the main challenges of foreign policy analysis in contemporary politics. After introducing the ways in which foreign policy analysis is addressed in the internationalist political literature, with a focus on policy formulation and decision-making understood as public policy, the authors focus on some of the main challenges that foreign policy scholars are called upon to face. In particular, the themes of (de)globalization and (dis)information are deepened, pointing out the reinforcement of the state and the risks connected to an increasing cognitive confusion.